Effects of inulin-type fructans supplementation on cardiovascular disease risk factors: a protocol for a systematic review and meta-analysis of randomised controlled trials - Russell J de Souza; Lawrence Mbuagbaw; John L Sievenpiper; Dena Zeraatkar; Laura Banfield; Vanessa Ha; David J A Jenkins; Jhalok Ronjan Talukdar; Matthew Adam Cooper; Lyuba Lyutvyn; Rahim Ali; Rachel Bierbrier; et al. (BMJ Open, 2022)
Introduction This review aims to assess the effects of dietary supplementation with inulin-type fructans (ITF) compared with no supplementation on cardiovascular disease risk factors in adults and assess the quality of trial reporting using the Consolidated Standards of Reporting Trials (CONSORT) and CONSORT for abstract (CONSORT-A) checklists.Methods and analysis We will search randomised controlled trials (RCTs) in MEDLINE, EMBASE, CINAHL, Emcare, AMED and the Cochrane Database of Systematic Reviews from inception to 31 March 2022, without any language restrictions. The RCTs need to administer ITF in adults for at least 2 weeks and assess effects on at least one cardiovascular risk factor. We will exclude RCTs that (1) assessed the postprandial effects of ITF; (2) included pregnant or lactating participants; (3) enrolled participants undergoing treatment that might affect the response to ITF. We will assess the study risk of bias (RoB) using V.2 of the Cochrane RoB tool for RCTs (RoB 2) and the certainty of the evidence using the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) approach. We will pool data using a random-effects model. We will use the χ2 test to compare compliance of CONSORT and CONSORT-A checklists and Poisson regression to identify factors associated with better reporting.Ethics and dissemination Ethics approval is not required for secondary analysis of already published data. We will publish the reviews in a peer-review journal.PROSPERO registration number CRD42019136745.